A Robust and Conductive Black Tin Oxide Nanostructure Makes Efficient Lithium‐Ion Batteries Possible. Issue 24 (21st April 2017) - Dong, Wujie; Xu, Jijian; Wang, Chao; Lu, Yue; Liu, Xiangye; Wang, Xin; Yuan, Xiaotao; Wang, Zhe; Lin, Tianquan; Sui, Manling; Chen, I‐Wei; Huang, Fuqiang
Abstract : SnO2 ‐based lithium‐ion batteries have low cost and high energy density, but their capacity fades rapidly during lithiation/delithiation due to phase aggregation and cracking. These problems can be mitigated by using highly conducting black SnO2− x, which homogenizes the redox reactions and stabilizes fine, fracture‐resistant Sn precipitates in the Li2 O matrix. Such fine Sn precipitates and their ample contact with Li2 O proliferate the reversible Sn → Li x Sn → Sn → SnO2 /SnO2− x cycle during charging/discharging. SnO2− x electrode has a reversible capacity of 1340 mAh g −1 and retains 590 mAh g −1 after 100 cycles. The addition of highly conductive, well‐dispersed reduced graphene oxide further stabilizes and improves its performance, allowing 950 mAh g −1 remaining after 100 cycles at 0.2 A g −1 with 700 mAh g −1 at 2.0 A g −1 . Conductivity‐directed microstructure development may offer a new approach to form advanced electrodes. Abstract : Changing oxide conductivity alone suffices for improving the lithiation/delithiation reversibility of tin‐oxide lithium‐ion batteries . The use of highly conductive black SnO2− x initiates homogeneous microstructure evolutions, forming very fine Sn particles inside the Li2 O to sustain reversible Sn redox, thus delivering durable capacitance. The addition of highly conducting, well‐dispersed reduced graphene oxide further improves the cycling performance.